Usefulness of the Córdoba Equation for Estimating Body Fat When Determining the Level of Risk of Developing Diabetes Type 2 or Prediabetes - Marta Marina Arroyo; Ignacio Ramírez Gallegos; Hernán Paublini; Ángel Arturo López-González; Pedro J. Tárraga López; Cristina Martorell Sánchez; Tomás Sastre-Alzamora; José Ignacio Ramírez-Manent (Medicina)
Background and Objectives: Type 2 diabetes (T2D) and prediabetes represent major global health concerns, with obesity being a key risk factor. However, recent evidence suggests that the adipose tissue composition and distribution play a more critical role in metabolic dysfunction than the total body weight or body mass index (BMI). This study evaluates the predictive capacity of the Córdoba Equation for Estimating Body Fat (ECORE-BF) for identifying individuals at high risk of developing T2D and prediabetes. Materials and Methods: A cross-sectional study was carried out involving 418,343 Spanish workers. Body fat percentage was estimated using the ECORE-BF equation, and diabetes risk was assessed using validated predictive models, including the Finnish Diabetes Risk Score (FINDRISC), QDiabetes score (QD-score), and others. The discriminatory power of ECORE-BF in predicting T2D and prediabetes was assessed using receiver operating characteristic (ROC) curve analysis. Results: ECORE-BF showed a strong correlation with high-risk classifications across all diabetes risk scales. The area under the ROC curve (AUC) exceeded 0.95 for both men and women, demonstrating high predictive accuracy. Conclusions: Adipose tissue distribution, particularly visceral adiposity, is a central factor in metabolic dysfunction. ECORE-BF provides a cost-effective alternative for large-scale T2D and prediabetes risk assessment. Future research should explore the impact of visceral adipose tissue reduction on diabetes prevention and the integration of estimation scales into clinical and public health strategies.